You'll never walk alone: Loneliness, religion, and politico‐economic transformation - Annie Tubadji (Politics and Policy)
The rise of subversive religious beliefs has been recently documented as related to politico-economic radicalization of places that feel left behind. When is the traditional local religious institution so socio-economically inefficient in providing hope for ‘not walking alone’ to become substituted by subversive religious beliefs on the market for hope? This paper suggests a detailed methodology, linking micro and macro levels, that starts from the quantification of the individual gain from religion as a source for well-being by providing the feeling of “not walking alone”. This micro gain is next used: (i) to evaluate a religious institution in terms of the social welfare that it generates, and (ii) to monitor this religious institution for losing its market to subversive religious beliefs, related to radical politico-economic transformations. To illustrate this methodology, the paper analyses the socio-economic efficiency of the Church of England as a predictive tool for the Brexit-vote.